The effect of daily sedation interruption protocol on early incidence of ventilator-associated pneumonia among patients hospitalized in critical care units receiving mechanical ventilation - Mehdi Shahabi; Hojatollah Yousefi; Ahmad Reza Yazdannik; Babak Alikiaii (Wolters Kluwer Medknow Publications, 2016)
Background: Ventilator-associated pneumonia (VAP) is a common side effect in patients who receive intravenous sedation infusion. In routine care, after starting sedation infusion for patients who receive mechanical ventilation, interruption of sedation starts without protocol. This study aimed to evaluate the effect of daily sedation vacation protocol on the incidence of VAP in mechanically ventilated patients. Materials and Methods: In this clinical trial study, 80 patients with intravenous sedation infusion were selected and randomly allocated to intervention and control groups. In the intervention group, daily sedation vacation protocol and in the control group, routine sedation vacation was followed. Modified clinical pulmonary infection score questionnaire was completed before intervention and on the third, fourth, and fifth days after intervention. Data were analyzed by using repeated measures analysis of variance (ANOVA), Chi-square, and independent t-test. Results: The results of this study showed that the incidence rate of VAP in the intervention and control groups was 0% versus 15% on the third day of intervention, 12.5% versus 50% on the fourth day, and 27.5% versus 55.3% on the fifth day of intervention in the intervention and control groups, respectively. The incidence of VAP in the intervention group was significantly lower than in the control group (P < 0.05). Conclusions: The results of this study showed that in patients with intravenous sedation, infusion of a daily sedation vacation protocol may reduce the incidence of VAP. Therefore, in order to prevent VAP, nurses are recommended to use this daily sedation vacation protocol.